Acquisition of LINE Digital Social Media Evidence Using the National Institute of Justice (NIJ) Method - Pawitradi, Gede; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Nowadays the use of social media has developed very rapidly over time. With very easy to use and also higher security than ordinary messaging services, making one of the factors of social media is very often used in today's world. But behind it all, social media such as LINE is very vulnerable to become one of the crime facilities, one of which is cyberbullying. To follow up on the cyberbullying activity, a forensic cellphone needs to be carried out to find evidence which is then useful to send to court. This study uses the LINE application as cyberbullying crime media, as well as using the National Institute of Justice (NIJ) method. The National Institute of Justice (NIJ) method has five basic stages namely, preparation, collection, examination, analysis, and reporting. In this study using the MOBILedit Forensic tool, and DB Browser for SQLite. It is hoped that the research carried out can help in solving cyberbullying on social media LINE on mobile forensics